Pengaruh Rasio Kas, Working Capital TurnOver, Solvabilitas, Tingkat Suku Bunga terhadap Profitabilitas - Siska Krisjayanti; Siti Tiffanny Guci; Erick Erick (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2019)
The purpose of this study was to test and diagnose the effect of cash ratios, working capital turnover, solvency, interest rates on profitability (Emprising studies on various industries listed on the Indonesia Stock Exchange. The theory used in this study was the theories of Cash Ratio, Working Capital Turnover, Solvency, Interest Rate.The research method used is descriptive quantitative, this research is causal / clausal.In this study, data collection was carried out through documentation studies.The study used types and secondary data sources.The results of this study were the Cash Ratio, Working Capital Turnover, Solvency, Interest Rate, simultaneously have a not positive and significant effect on the firm value of empirical studies on Various Industries listed on the Stock Exchange for the period 2013-2016. The conclusions in this study are Cash Ratio, Working Capital Turnover, Solvency and Interest Rates are partially taxed not positive and significant spirit towards the value of empirical studies on Various Industries listed on the IDX for the period 2013-2016